Expanding Diversity of Susceptible Hosts in Peste Des Petits Ruminants Virus Infection and Its Potential Mechanism Beyond - Dou, Yongxi; Liang, Zhongxiang; Prajapati, Meera; Zhang, Rui; Li, Yanmin; Zhang, Zhidong (Frontiers in Veterinary Science, 2020)
Peste des petits ruminants (PPR) is a severe respiratory and digestive tract diseases of domestic small ruminants, caused by PPR virus (PPRV) of the genus Morbillivirus. Although the primary hosts of PPRV are goats and sheep, the host range of PPRV has been continuously expanding and reported to infect various animal hosts over last decades, which could bring a potential challenge to effectively control and eradicate PPR globally. In this review, we focused on the current knowledge about host expansion and interspecies infection of PPRV and discussed the potential mechanisms involved.